The State of the World's Children 1992 - Grant, James P. (United Nations Children's Fund (UNICEF), 1992)
This contains two parts: Part I – The State of the World’s Children 1992, which looks at the agenda for a new order as well as the following headings: 1. Keeping the promise, 2. First call for children, 3. Fewer deaths, fewer births, 4. Investing in people, 5. Aid and need, 6. The economic environment, 7. Disarmament, 8. Setting Africa free, 9. The apartheid of gender, and 10. Planning births. Part II – Statistics, which looks at economic and social statistics on the nations of the world, with particular reference to children’s well-being.
Keywords: Children